Health communication campaigns: A brief introduction and call for dialogue - Xiaoquan Zhao (Elsevier, 2020)
This article provides a brief introduction to health communication campaigns as an important method for health promotion. The general approach to campaign development is described and patterns of campaign effects across behavioral contexts are noted. Several high-profile campaigns in the United States are presented as examples and key learnings from each campaign are highlighted. The roles of theory, as well as major types of theories commonly used in campaign research, are also discussed. The article urges greater efforts to document and understand diverse campaign experience around the world.